PENGARUH KOMUNIKASI PEMASARAN TERHADAP PENINGKATAN JUMLAH NASABAH ASURANSI BUMI ASIH JAYA MEDAN - Ardial Ira Yustina (PERSPEKTIF, 2016)
This research is conducted to know how execution of marketing communications by employees of Glorious Earth Asih Insurance. The issues of this research is: " How far the iInfluence of marketing communications to make-up of the amount of client at Glorious Earth Asih Insurance?" Research Method used by method korelasional, while technique of data collecting is by propagating enquette. Technique analyse the data used in this research analyse the single tables. Result of research indicate that the level of correlation obtained is equal to 0,658, this value far reside in to the r table that is equal to 0,2848. Result test the Z calculate obtained by r = 14 compared to by bigger[of value rXY = 0,658. Hence inferential that free influence of X of marketing Communications to variable tied by Y ( make-up of the amount of client) is significant. Mean the hypothesis raised to be accepted. Pursuant to coefficient determinasi known by that level of influence of marketing communications to make-up of the amount of client is equal to 43,296% and the rest of equal to 61,06% influence by other factor outside this research